When the Quality of a Nation triggers Emigration - Hendrik P. van Dalen; Kène Henkens (Tinbergen Institute, 2006)
Why do people leave high-income countries with extensive welfare states? This article will examine what underlies the emigration intentions of native-born inhabitants of one industrialized country in particular: the Netherlands. To understand emigration from high-income countries we focus not only on factors that refer to individual characteristics, but also on the perception of the quality of the public domain, which involves institutions (social security, educational system, law and order) as well as the 'public goods' these institutions produce: social protection, safety, environmental quality, education, etc. Based on data about the emigration intentions of the Dutch population collected during the years 2004-2005 we conclude that besides traditional characteristics of potential emigrants - young, single, male, having a network in the country of destination, higher educated, seeking new sensations - modern-day emigrants are motivated not so much by private circumstances but by a longing for a better public domain. In particular, emigrants are in search of a better quality of life as approximated by the presence of nature, space, silence, and a less populated country. To gauge the effect of the quality of the public domain, a counterfactual scenario is offered, which suggests that a perception of severe neglect of the public domain substantially increases the pressure to emigrate. Under this scenario, approximately 20 percent of the Dutch population would express an intention to emigrate. Compared with the level of emigration intentions measured today, this represents an increase by a factor of 5.
Keywords: F22; H4; J24; J61; 330; emigration; international migration; population pressure; public goods; externalities; brain drain